The Developing Brain: Considering the Multifactorial Effects of Obesity, Physical Activity & Mental Wellbeing in Childhood and Adolescence - Nicole E. Logan; Christie L. Ward-Ritacco (MDPI AG, 2022)
Obesity during childhood has been associated with many important physiological and neurological health considerations. Specifically concerning are the associations between youth obesity and declines in mental health, as shown with increasing rates of adolescent depression and anxiety worldwide. The emergence of mental health disorders commonly arises during adolescent development, and approximately half the global population satisfy the criteria for at least one psychiatric disorder in their lifetime, suggesting a need for early intervention. Adolescence is critical time whereby brain structure and functions are not only negatively associated with obesity and declines in mental health, while also coinciding with significant declines in rates of physical activity among individuals in this age group. Physical activity is thus a prime candidate to address the intersection of obesity and mental health crises occurring globally. This review addresses the important considerations between physiological health (obesity, aerobic fitness, physical activity), brain health (structure and function), and mental wellbeing symptomology. Lastly, we pose a theoretical framework which asks important questions regarding the influence of physiological health on the association between brain health and the development of depression and anxiety symptoms in adolescence. Specifically, we hypothesize that obesity is a mediating risk factor on the associations between brain health and psychopathology, whereas physical activity is a mediating protective factor. We conclude with recommendations for promoting physical activity and reducing sedentary time.